Clinical, epidemiological and epizootic features of a Q fever outbreak in the border region between Serbia and Montenegro - Zoran Debeljak; Snezana Medić; Marija Baralić; Aleksandra Andrić; Aleksandar Tomić; Dejan Vidanović; Milanko Šekler; Kazimir Matović; Nikola Vasković (Journal of Infection in Developing Countries)
Introduction: Q fever is a zoonosis which commonly manifests as an acute febrile disease accompanied by pneumonia or hepatitis. The aim of this study was to reveal the reservoirs, sources and routes of infection relevant for the Q fever outbreak that occurred in the border region between Serbia and Montenegro.